Recollecting: Lives of Aboriginal Women of the Canadian Northwest and Borderlands - Sarah Carter (The West Unbound:Social and Cultural Studies, 2011)
Recollecting is a rich collection of essays that illuminates the lives of late-eighteenth-century to mid-twentieth-century Aboriginal women, who have been overlooked in sweeping narratives of the history of the West. Some essays focus on individuals-a trader, a performer, a non-human woman. Other essays examine cohorts of women-wives, midwives, seamstresses, nuns. Authors look beyond the documentary record and standard representations of women, drawing on records generated by the women themselves, including their beadwork, other material culture, and oral histories. Exploring the constraints and boundaries these women encountered, the authors engage with difficult and important questions of gender, race, and identity. Collectively these essays demonstrate the complexity of "contact zone" interactions, and they enrich and challenge dominant narratives about histories of the Canadian Northwest.